2021
DOI: 10.3892/etm.2021.9862
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive gut microbial dysbiosis between chronic alcoholic fatty liver disease and metabolic‑associated fatty liver disease in mice

Abstract: The gut microbiota, which may affect normal physiological and biochemical functions, has an important role in the development of human liver diseases. The aim of the present study was to investigate differences in the gut microbiota between chronic alcoholic fatty liver disease (AFLD) and metabolic-associated fatty liver disease (MAFLD). AFLD was induced by chronic alcohol administration and MAFLD was induced by a Western-style diet in C57BL/6 mice. After 8 weeks, the levels of plasma alanine aminotransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
2
17
0
Order By: Relevance
“…[ 7 ] Thus, we analyzed the gut microbiota characters by 16S rRNA sequencing. The effects of alcohol on alpha diversity of gut microbiota are still controversial, [ 48,49 ] and our present study supported that alcohol can lead to alpha diversity elevation. Previous studies reported that alcohol feeding caused a reduction in Bacteroidetes and an increase in Firmicutes, [ 9 ] which was furtherly supported by our study.…”
Section: Discussionsupporting
confidence: 85%
“…[ 7 ] Thus, we analyzed the gut microbiota characters by 16S rRNA sequencing. The effects of alcohol on alpha diversity of gut microbiota are still controversial, [ 48,49 ] and our present study supported that alcohol can lead to alpha diversity elevation. Previous studies reported that alcohol feeding caused a reduction in Bacteroidetes and an increase in Firmicutes, [ 9 ] which was furtherly supported by our study.…”
Section: Discussionsupporting
confidence: 85%
“…In a study on mice by Kang et al, distinctive GM dysbiosis was observed in chronic alcoholic fatty liver disease (AFLD) and metabolic-associated fatty liver disease (MAFLD). Compared to controls, the AFLD group had significant abundance of Enterococcus and Streptococcus, and in the MAFLD group, Lachnospiraceae was the most abundant bacterial family, Erysipelatoclostridium, Gordonibacter, and Streptococcus were the most abundant bacterial taxa, and there was a reduction of Bifidobacterium (15). Researchers from China showed that GM composition and structure significantly change with ALD progression and that the relative abundance of Streptococcus species significantly increases in alcohol-associated cirrhosis and correlates positively with aspartate aminotransferase level.…”
Section: Preclinical Studies On the Role Of Gm In Aldmentioning
confidence: 99%
“…High-fat diet (HFD) feeding is an ideal and widely used method to induce hepatic steatosis, and the process is accompanied by the changes of bile acid (BA) metabolism and gut microbiota. Our previous studies have shown the alleviative effects of apple polyphenol extract (APE) on hepatic steatosis by activating the SIRT1/AMPK signaling pathway in vitro and in vivo. , However, the mechanisms are still not thoroughly elucidated.…”
Section: Introductionmentioning
confidence: 99%